Pengelolaan Pembelajaran Akuntansi di SMK - Utami, Lilis Retno; Subadi, Tjipto (Universitas Muhammadiyah Surakarta, 2016)
Aim of the research are to describes planning, organizing, actuating and evaluating of Accounting Learning At State Vocational High School 1 Of Sragen. The research type is qualitative research with etnography design. Data was collected by interview, observation and documentation. Data analysis technique using an interactive model of analysis. Results of this research concluded that: 1) Accounting RPP preparation begins with studying the content standards, competency standards, syllabus, prepare lesson plans, 2) Organizing Accounting learning includes organizing the subject matter sequentially in accordance with the syllabus reference, academic calendar, class, difficult subject matter and to find a settlement, 3) Accounting learning process begins with teachers delivering salutation, attention or observation of hygiene class, do absent students, check homework assignments, and motivates students, 4) Accounting learning evaluation by sharing test questions to students. Accounting learning practice test indicated by the ability to make financial reports. Teacher do remedial to students who have value is below the minimum completeness criteria, instead of teachers provide enrichment for students who value above minimum completeness criteria. Spesific model of Accounting learning is scientific performance sheet.